2020
DOI: 10.3991/ijet.v15i06.12003
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Open Access of Institutional Electronic Research Corners for Promotion of Communication Facilities and Quality Research

Abstract: Indian higher education institutions (HEIs) are struggling hard to get a berth among top-rated HEIs in the world. One of the important parameters that restrict our HEIs from the list of top-notch global HEIs is ‘contribution to research’. It does not mean that Indian HEIs don’t have quality researchers to produce world class research output. Had that been the case, Indian researchers doing research abroad would not have done miracles with their unique research output in varied domains. The hindrance for resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies had identified the Acceptance of OA as well as the Arguments promoting OA [9]. The Tools trend includes works related to the tools aimed at facilitating the development, use, or access to digital resources are included, by integrating different resources [38,40,50], complementing the integration efforts [58], presenting the elements necessary for developing and publishing open academic courses, and allowing different national standards to be compatible [66]. Previous works don't seem to address the tools as such but in the relation to the actors that use some OA resources [11] or see them as a part of the technical barriers [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies had identified the Acceptance of OA as well as the Arguments promoting OA [9]. The Tools trend includes works related to the tools aimed at facilitating the development, use, or access to digital resources are included, by integrating different resources [38,40,50], complementing the integration efforts [58], presenting the elements necessary for developing and publishing open academic courses, and allowing different national standards to be compatible [66]. Previous works don't seem to address the tools as such but in the relation to the actors that use some OA resources [11] or see them as a part of the technical barriers [11].…”
Section: Discussionmentioning
confidence: 99%
“…A group of authors focused their attention on the "Austrian Transition to Open Access (AT2OA)", authorized by the Austrian Federal Ministry of Science, Research and Economy [19,33,35,[38][39][40][41]. According to [29] in this project, running from 2017 to 2020, "the 21 public universities cooperate to promote OA through concerted measures" [29].…”
Section: Financial Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is desirable for teachers' efforts to exchange ED to be supported by the appropriate educational policy on the control of research quality at the level of the department, higher educational establishment, state, the academic community, etc. We did not aim to develop special recommendations because we consider it reasonable to start by implementing a complex of measures at the institutional and individual levels for strong support of Open Science (Swain, 2020), as proposed by the scientists of the National Academy of Educational Sciences of Ukraine.…”
Section: сOnclusionmentioning
confidence: 99%
“…implementation of the principles of Open Science in scientific and educational spheres (Swain, 2020);  modernization of the main priority areas of psychological and pedagogical research and updating the training content for academic staff (Sovetkanova et al, 2021);  appropriate scientific support for the creation of national educational and information spaces (Santoso et al, 2019;Musa, 2019;  use of electronic systems with open access to facilitate quality research (Spirin et al, 2017);  raising teachers' awareness of the ways and prospects of informatization of education (Zhornova & Zhornova, 2014) and the use of innovative pedagogical and digital technologies, Web 2.0 services in the educational process, etc. (Revenko, 2021);  research into innovative methods of education and information and communication technologies developed in Ukraine and abroad (in particular, online platforms for distance learning) to improve the quality of the educational process (Mann et al, 2020);  the use of Open Educational Resources by teachers (Guo et al, 2015), etc.…”
mentioning
confidence: 99%